2017
DOI: 10.1108/ijbm-10-2016-0155
|View full text |Cite
|
Sign up to set email alerts
|

Does willingness-to-pay for weather index-based insurance follow covariant shocks?

Abstract: Purpose The purpose of this paper is to investigate the role that weather shocks can play in the livestock mortality microinsurance take-up when the insured risk has a prevalent covariant component. Design/methodology/approach The sample consists of 360 rural Ethiopian households. Data were collected in a panel-structure at the end of three agricultural seasons (2011-2013). In the questionnaire, a specific section on insurance was meant to collect information on the farmer’s willingness-to-pay (WTP) for a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The average age of the farmers choosing WII was 2.5 years younger than that of the other group. This is consistent with the study by Castellani and Viganò (2017), who found that older farmers and those with a limited understanding of insurance tend to be less willing to pay for insurance. A potential explanation may be that they are less able to understand the value and claims mechanism of weather index insurance.…”
Section: What Are the Characteristics Of Farmers In Different Risk Management Strategies?supporting
confidence: 92%
See 1 more Smart Citation
“…The average age of the farmers choosing WII was 2.5 years younger than that of the other group. This is consistent with the study by Castellani and Viganò (2017), who found that older farmers and those with a limited understanding of insurance tend to be less willing to pay for insurance. A potential explanation may be that they are less able to understand the value and claims mechanism of weather index insurance.…”
Section: What Are the Characteristics Of Farmers In Different Risk Management Strategies?supporting
confidence: 92%
“…This means that with more laborers engaged in non-farming activities, households would rely less on agriculture and their demand for agricultural insurance would be lower. Off-farm activities increase households' income sources and improve their ability of risk diversification (Castellani and Viganò 2017), so farmers do not need to purchase agricultural insurance to deal with risks. The coefficients for agricultural insurance purchase experience are all positive and significant in Models 1-4.…”
Section: Regression Analysismentioning
confidence: 99%
“…Farmers expect a good insurance system and indemnity payment with a satisfactory payment process (Karthick et al, 2017). A crop insurance product itself should give farmers an understandable picture of an insurance scheme (Castellani and Vigano, 2017). A reasonable insurance premium and a well-organized indemnity payment process influence farmers' confidence leading to continuous crop insurance participation (Wang et al, 2016).…”
Section: Crop Insurance Developmentmentioning
confidence: 99%
“…In the context of insurance, several articles empirically examine WTP in developing countries for crop insurance (see, e.g., Bulte et al, 2019; Freudenreich & Mußhoff, 2018; Wang et al, 2020), health insurance (see, e.g., Bonan et al, 2014; Delavallade, 2017), livestock insurance (see, e.g., Castellani & Vigan'o, 2017), different types of index and microinsurance in different parts of the world (see, e.g., Elabed & Carter, 2015), flood insurance (see, e.g., Botzen & Bergh, 2012), and weather insurance (see, e.g., Fraser, 1992; Musshoff et al, 2008). For developed countries, analyses of WTP for insurance tend to focus on public social systems.…”
Section: Literature Reviewmentioning
confidence: 99%